First direct evidence of adult European eels migrating to their breeding place in the Sargasso Sea - Wright, Rosalind M.; Piper, Adam T.; Aarestrup, Kim; Azevedo, Jose M. N.; Cowan, George; Don, Andy; Gollock, Matthew; Ramallo, Sara Rodriguez; Velterop, Randolph; Walker, Alan; Westerberg, Håkan; Righton, David (2022)
The European eel (Anguilla anguilla) is critically endangered (according to the most recent IUCN assessment) and has suffered a 95% decline in recruitment since the 1980s, attributed in part to factors occurring during the marine phases of its life-cycle. As an adult, the European eel undertakes the longest spawning migration of all anguillid eels, a distance of 5000 to 10,000 km across the Atlantic Ocean to the Sargasso Sea. However, despite the passage of almost 100 years since Johannes Schmidt proposed the Sargasso Sea as the breeding place of European eels on the basis of larval surveys, no eggs or spawning adults have ever been sampled there to confirm this. Fundamental questions therefore remain about the oceanic migration of adult eels, including navigation mechanisms, the routes taken, timings of arrival, swimming speed and spawning locations. We attached satellite tags to 26 eels from rivers in the Azores archipelago and tracked them for periods between 40 and 366 days at speeds between 3 and 12 km day(-1), and provide the first direct evidence of adult European eels reaching their presumed breeding place in the Sargasso Sea.